Pre-service teachers’ conceptions about the quality of explanations for the science classroom in the context of peer assessment - Cabello, Valeria; Topping, Keith J. (LUMAT: International Journal on Math, Science and Technology Education, 2020)
This study explored student-teacher conceptions of explanations for the science classroom during teacher education programs through peer-assessments of 20 pre-service teachers from three universities. The peer-assessments were reciprocal and focused on the explanation of scientific concepts during microteaching episodes. Student-teacher conceptions about the quality of scientific explanations were obtained by analysing their assessment-feedback comments to peers and by focus groups. The results showed that student-teacher conceptions about the quality of explanations for the science classroom were related to constructivist theory applied to science teaching, for instance, the participants noticed that better explanations were those that connected the concepts with the students’ ideas and experiences. A follow-up with a sub-sample of six participants during a practicum in schools explored through interviews the perceived enablers and obstacles that affected their explanation construction in real settings leading to reframing their conceptions. This study revealed that peer assessment and feedback could play a significant role in teacher education by eliciting student-teacher conceptions about essential teaching practices and the challenges of explaining in real teaching, which might enhance and empower their skill development. We discuss implications for research and practice, with emphasis on peer assessment as a tool for internalising assessment criteria for fruitful science teaching.